PARTICIPATION OF WOMEN IN CONSTRUCTION BATTALIONS DURING THE GREAT PATRIOTIC WAR (1941-1945) (ON MATERIALS OF THE SOUTH OF RUSSIA) - G. N. Kameneva (Гуманитарные и юридические исследования)
This article raises a poorly developed question from the historical point of view regarding recruitment of women for the hardest military construction work including battle performance during the Great Patriotic War. With the reference to materials of the south of Russia the activity of road-exploitation and defense-building military regiments women contingent, their department subordination, volumes and problems of building work realization in region, mechanisms of female civil population resources use are analyzed. The aspects of functionality, women-builders service conditions are discussed and some examples of military biographies are presented. The article presents new archive data about female population of North-Caucasus fronts' construction columns.